MODEL ARSITEKTUR POHON ARBORETUM UNIVERSITAS LANCANG KUNING SEBAGAI PENUNJANG PEMBELAJARAN - Hadinoto, Hadinoto; Suhesti, Eni (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
Arboretum is an example of forest which is a collection of trees which is a form of conservation of human-made germplasm. Arboretum with various vegetation containing scientific values ​​can be used as an open laboratory for student education and research facilities. The pattern of branching plants will form a form of plant architecture. The branching architecture is a morphological representation of a particular phase of a series of tree growth series, real and observable at all times. This research was conducted by conducting a survey (survey) and direct observation of the model of bamboo branching architecture in plants located in the research location. Identification of tree architecture model using book by F. Halle & R.A.A.Oldeman, namely: An Essay On The Architecture and Dynamics of Growth of Tropical Trees. Each tree is observed and photographed, as research documentation. Analysis conducted in this research is descriptive analysis to the type and shape of architectural architecture of Arboretum University of Lancang Kuning. Based on the results of research that has been done, can be drawn conclusion as follows: obtained 10 shapes / models of tree architecture of 41 species of trees (diamater 20 cm).